Balanced polymorphism in a floral transcription factor underlies the ancient rhythm of daily sex alternation in avocado - Jeffrey S. Groh; Marllon F. Soares dos Santos; Emmanuel Avila de Dios; Gracie Ackerman; Edwin Solares; Rodrigo A. Iturrieta; Eric Focht; Danelle Seymour; Brandon S. Gaut; Mary Lu Arpaia; Graham Coop (Proceedings of the National Academy of Sciences, 2026)
In avocado and certain wild relatives in Lauraceae, a highly synchronized daily rhythm of floral sex timing promotes cross-pollination between two hermaphroditic flowering types. A-type plants present female-phase flowers in the morning and male-phase flowers in the afternoon, while B-types show the complementary pattern—a form of heterodichogamy. We mapped this dimorphism to a pair of dominant and recessive haplotypes at SDMYB , which belongs to a subgroup of R2R3 MYB transcription factors established as key regulators of floral maturation with links to circadian hormone signaling. Rhythmic diel SDMYB expression is associated with biphasic floral anthesis, and the dominant allele, which contains nonsynonymous changes in conserved functional domains, exhibits a cis -regulated phase delay, corresponding to the delayed second anthesis of A-type flowers. The SDMYB haplotypes form an ancient trans-species polymorphism, maintained by negative frequency-dependent balancing selection over 42 My, and they segregate in at least 26 nonavocado species, including in a genus where this mating system has not been reported. Although exceptionally old, the polymorphism is absent in other magnoliids with highly similar mating systems, suggesting daily forms of heterodichogamy can convergently evolve when rhythmic floral movements are coupled with the temporal separation of sexes.